Polska międzywojenna myśl polityczna i społeczna wobec rasizmu i higieny rasowej w Trzeciej Rzeszy - Musielak, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The aim of the article was to present the stand point of chosen Polish politicians and publicists of the II Republic era towards racism and Nazi eugenics. Basing on a thorough analysis of the writings of national democratic, Christian politicians and ideologists of the political system called “sanacja”, the author described their perspective on the legal and political practices of the Third Reich aimed at Jews and people considered eugenically “unfit”. The author discussed the reasoning behind Hitler’s anti-Semitic politics and racial hygiene, as presented in the Polish writings of the mid-war era. The attempts to introduce similar practices in Poland were further presented.Translated by Michał Musielak
Keywords: Second Republic of Poland; racism; eugenics; political thought; Third Reich German